(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
The article reveals new requirements for the training of vocational education specialists and their analysis of professional qualities, to be able to apply comprehensive knowledge in various disciplines in their professional activities. And quick adoption of optimal decisions in any complex professional situations in which the formation of skills to independently perform certain actions can be carried out using an interdisciplinary approach.